Spillover Effects of Fraud Allegations and Investor Sentiment - Darrough, Masako; Huang, Rong; Zhao, Sha (Contemporary Accounting Research, 2020)
ABSTRACT We examine whether a stock price spillover effect spreads through the method of listing or country of origin and whether this spillover effect changes when investor sentiment shifts. Using a sample of fraud allegations against Chinese companies that became public through Chinese reverse mergers (CRMs), we investigate whether firms that experienced negative spillover effects on their stock prices are those from the same country and/or with the same method of listing as the firms accused of fraud. We first show that the negative spillover effect channeled through the firm's country of origin becomes stronger when investor sentiment about Chinese companies becomes pessimistic, as evinced by significant declines in the stock prices of non‐fraudulent Chinese companies, including both CRMs and Chinese IPOs. Second, we show that the negative spillover effects on CRMs are stronger than those on Chinese IPOs and non‐Chinese reverse mergers, suggesting that both country and listing method are applicable to CRMs. Our findings indicate that (i) investor sentiment plays an important role in the spillover process involving fraud allegations and (ii) while the two channels could coexist, negative spillover effects that spread through the country of origin play a more prominent role than those that spread through the method of listing.